KEPEMIMPINAN KEPALA PONDOK PESANTREN DALAM MENGIMPLEMENTASIKAN PROGRAM LINGKUNGAN BERBAHASA ARAB DI PONDOK PESANTREN DARUTTAUHID MALANG - Mochammad Faris Aresy (Leadership: Jurnal Mahasiswa Manajemen Pendidikan Islam, 2020)
Communicating using Arabic is an obligation that must be done by students at Daruttauhid Islamic Boarding School in Malang. In implementing this policy it is necessary to have a figure to emulate who can also guide, and direct the civitas in shaping the Arabic language environment so that all process activities are carried out properly and smoothly. The purpose of this study is to describe the leadership and efforts of the head of Islamic boarding school in implementing the Arabic language environment program along with its supporting and inhibiting factors. This research uses descriptive qualitative research methods, with the type of case study research, where the research location is Daruttauhid Islamic Boarding School Malang. The data is obtained directly from the head of the hut and other competent parties in the hut. The process of collecting data uses interview observation and documentation techniques which are analyzed descriptively through the editing process with the stages of data reduction, data presentation, and drawing conclusions. From the results of this study indicate that (1) The leadership of Islamic boarding school heads in Daruttauhid Islamic Boarding School in Malang in implementing Arabic language programs using the type of authoritarian leadership that can be seen in the programs and regulations of Islamic boarding schools that run in an orderly and conducive manner and and sometimes with democratic leadership it can be seen with the monthly meetings and harmonious relations between the head of the hut with the religious teachers and students.(2) The efforts of the head of the boarding school at the Daruttauhid in developing an Arabic language environment program include forming a santri organization namely language section, holding Arabic conversation, provisioning Arabic vocabulary, additional lessons for basic class, Arabic speech training, watching films in Arabic. (3) Supporting factors that can launch this Arabic-language environmental activity are the religious teachers here are the majority of Middle Eastern graduate. The inhibiting factors are facing new students who cannot speak Arabic and students who are ashamed to express their words, the mixing of Indonesian or Javanese with Arabic.